Organizational Commitment as A Moderator of Budget Participation with Budget Gaps - Diah, Widyanti; Puspita, Nolla (Universitas Batam, 2023)
This research examines the relationship between participation budgets and participation budgets involving organizational commitment. The aim of this research is to determine the effect of organizational commitment as a moderating variable between the correlation between budget participation and budget accounting. This research uses primary data obtained by distributing questionnaires to respondents non-randomly. The unit of analysis for this research is individuals, namely managers consisting of marketing managers, sales managers, financial managers, production managers and other department managers. Sample collection was carried out using a purposive sampling method which was carried out at one time within a period of one year and one month (one-stage-study). This research succeeded in testing that the moderating variable commitment influences the organization influencing individual participation in budget preparation, and accepted the research hypothesis that there is a significant influence between the independent interaction variables on the dependent variable.